1999
DOI: 10.1037/0278-6133.18.5.506
|View full text |Cite
|
Sign up to set email alerts
|

A meta-analysis of psychoeducational programs for coronary heart disease patients.

Abstract: In a meta-analysis of 37 studies, the effects of psychoeducational (health education and stress management) programs for coronary heart disease patients were examined. The results suggest that these programs yielded a 34% reduction in cardiac mortality; a 29% reduction in recurrence of myocardial infarction (MI); and significant (p < .025) positive effects on blood pressure, cholesterol, body weight, smoking behavior, physical exercise, and eating habits. No effects of psychoeducational programs were found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
234
2
29

Year Published

2002
2002
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 425 publications
(276 citation statements)
references
References 53 publications
11
234
2
29
Order By: Relevance
“…Further, exercise interventions can reduce hypertension and depressive symptoms Blumenthal et al, 1999) and have been found to increase heart rate variability among CHD patients (Stahle, Nordlander, & Bergfeldt, 1999). Hence, unless medically contraindicated, the broad psychological and physiological benefits of exercise (Dubbert, 2002;Salmon, 4 It is important to note that this pattern of outcomes is inconsistent with the meta-analytic finding of Dusseldorp et al (1999) in which interventions that improved psychosocial functioning were more likely to have beneficial effects of morbidity and mortality. However, additional-albeit preliminary-analyses from the ENRICHD trial indicate that the psychosocial intervention significantly reduced recurrent CHD events among White men (Schniederman, 2002).…”
Section: Implications For Patient Carecontrasting
confidence: 47%
See 1 more Smart Citation
“…Further, exercise interventions can reduce hypertension and depressive symptoms Blumenthal et al, 1999) and have been found to increase heart rate variability among CHD patients (Stahle, Nordlander, & Bergfeldt, 1999). Hence, unless medically contraindicated, the broad psychological and physiological benefits of exercise (Dubbert, 2002;Salmon, 4 It is important to note that this pattern of outcomes is inconsistent with the meta-analytic finding of Dusseldorp et al (1999) in which interventions that improved psychosocial functioning were more likely to have beneficial effects of morbidity and mortality. However, additional-albeit preliminary-analyses from the ENRICHD trial indicate that the psychosocial intervention significantly reduced recurrent CHD events among White men (Schniederman, 2002).…”
Section: Implications For Patient Carecontrasting
confidence: 47%
“…The most recent and complete of these (Dusseldorp, van Elderen, Maes, Meulman, & Kraaij, 1999) found evidence of beneficial effects and provided a potential explanation for inconsistent findings. Health education (e.g., targeted toward behavioral risk reduction) and stress management had equivalent significant effects on cardiac recurrences, producing on average a 34% reduction in cardiac mortality and a 29% reduction in recurrent MI.…”
Section: Findings From Quantitative Reviewsmentioning
confidence: 99%
“…Previous reviews have reported a reduction in mortality, [16][17][18] but were not fully systematic in their coverage and did not differentiate the different psychosocial and stress management interventions. 15 …”
Section: Effectiveness Of Cardiac Rehabilitationmentioning
confidence: 99%
“…A review of 37 studies showed a 34% reduction in cardiac mortality, 29% reduction in recurrence of MI and positive effects on blood pressure, cholesterol, body weight, smoking behaviour, physical exercise, and eating habits (Dusseldorp, Elderen, Maes, Meulman, & Kraaij, 1999). Cardiac rehabilitation is recognized by the UK government as a cost-effective approach to reduce future health problems (National Service Framework on Coronary Heart Disease, 2000; National Institute for Clinical Excellence, 2001).…”
Section: Introductionmentioning
confidence: 99%